Dental caries and gingivitis among 15 to 19 year-old students in Manaus, AM, Brazil - Maria Augusta Bessa Rebelo; Márcia Cristina Lopes; Janete Maria Rebelo Vieira; Rosana Cristina Pereira Parente (Sociedade Brasileira de Pesquisa Odontológica, 2009)
In the light of the scarcity of epidemiological studies on the oral health of the general population within the context of the Amazon region, this study aimed to estimate the prevalence of dental caries and gingivitis, as well as to evaluate the need for restorative treatment, among school students aged 15 to 19 years in the city of Manaus, AM, Brazil. A cross-sectional study was carried out on a sample of 889 students from within city limits who were enrolled in 26 public and private schools. Dental examinations were performed to obtain the DMFT index (decayed, missing and filled teeth) as well as to determine the treatments needed. The gingival index (Lõe & Silness) was used to classify gingivitis. The intra-examiner diagnostic concordance was 94% and the Kappa statistic was 0.91. The DMFT index found was 4.65 (± 0.12), without significant difference between the sexes or skin color groups. The prevalence of dental caries was 87.4%. Restoration of a dental surface was the greatest need (59.3%). Slight gingival inflammation was present in 78.5% and gingival bleeding following probing occurred in 53.3%. Although the DMFT index was lower than that observed for the northern region of Brazil, restorative dental services are lacking for this population. Additional studies are suggested to better understand the differences found.